The modulatory effects of biogenic amines on male mating performance in Bactrocera dorsalis - Wenlong Chen; Wenlong Chen; Yaoyao Chen; Yaoyao Chen; Ziwei Xiao; Ziwei Xiao; Yuhua Zhang; Yuhua Zhang; Tong Zhang; Guohua Zhong; Guohua Zhong; Xin Yi; et al. (Frontiers in Physiology, 2022)
In insects, the emergence of mating behavior requires the interplay among sex-determination hierarchy mechanisms that regulate sex-specific differentiation, perception and integration of different sensory cues, and precisely patterned behavioral outputs. Biogenic amines, including octopamine (OA), dopamine (DA), tyramine (TA), serotonin and histamine, have been identified and proposed as putative neurotransmitters, neurohormones and/or neuromodulators in the central nervous system of insects to influence multiple physiologies and behaviors. The current study provides the physiological roles and pharmacology of these biogenic amines in the mating performance of Bactrocera dorsalis. Silencing gene expressions coding for biosynthetic enzymes of DA and serotonin in male flies could decrease mating rates, while OA, TA and histamine had no such effects on mating. Furthermore, injection of DA or the DA receptor antagonist chlorpromazine could affect mating rate, as well as injection of serotonin. Pharmacological treatments with other biogenic amines or their receptor antagonists in male flies have no roles in regulating mating performance. We conclude that DA and its receptors are involved in regulating male mating behaviors in B. dorsalis, while changes in serotonin levels in male flies could also affect mating rates. In the current study, the modulatory effects of these biogenic amines on mating performance were investigated, and these results will be helpful in providing a new strategy for controlling B. dorsalis.